From barriers to novel strategies: smarter CAR T therapy hits hard to tumors - Khawar, Muhammad Babar; Ge, Fei; Afzal, Ali; Sun, Haibo (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) T cell therapy for solid tumors shows promise, but several hurdles remain. Strategies to overcome barriers such as CAR T therapy-related toxicities (CTT), immunosuppression, and immune checkpoints through research and technology are needed to put the last nail to the coffin and offer hope for previously incurable malignancies. Herein we review current literature and infer novel strategies for the mitigation of CTT while impeding immune suppression, stromal barriers, tumor heterogeneity, on-target/off-tumor toxicities, and better transfection strategies with an emphasis on clinical research and prospects.